The cash crop revolution, colonialism and economic reorganization in Africa. (October 2022) - Roessler, Philip; Pengl, Yannick I.; Marty, Robert; Titlow, Kyle Sorlie; van de Walle, Nicolas
Highlights: Undertakes one of the first systematic analyses of the cash crop revolution on long-run development in Africa. Draws on data on the source location of 95% of all primary commodity exports across 38 African countries in late 1950s. Finds the path dependent effects of cash crop agriculture rival or surpass other geographic and historical forces. Shows that colonial infrastructure investments in cash crop zones account for larger shares of these effects than continued agricultural production. However, demonstrates these agglomerating effects were highly localized and tended to displace, rather than enhance, the economic potential of nearby areas. Abstract: In the 19th and 20th centuries, African economies experienced a significant structural transformation from the slave trades to commercial agriculture. We analyze the long-run impact of this economic transition focusing on the dynamic effects of: shifting geographic fundamentals to favor agro-climatic suitability for cash crops; infrastructural investments to reduce trade costs; and external forward production linkages. Using agro-climatic suitability scores and historical data on the source location of more than 95 percent of all exports across 38 African states, we assess the consequences of these changes on economic reorganization across the continent. We find that colonial cash crop production had positive long-run effects on urbanization, road infrastructure, nighttime luminosity, and household wealth. These effects rival or surpass other geographic and historical forces. Exploring causal mechanisms, we show that path dependence due to colonial infrastructure investments is the more important channel than continued advantages in agricultural productivity. However, these agglomerating effects were highly localized; we find limited evidence that commercial agriculture spurred broader regional growth, in contrast to other cash crop regions around the world. If anything, we observe in Africa the economic gains accruing to cash crop zones came at the expense of nearby areas, which are worse off today than expected based on underlying characteristics. Overall, our analysis has important implications for the debate on the long-run effects of colonialism on development in the region. Rather than offsetting negative institutional effects, subnational extractive processes may have reinforced them by sowing economic and social inequalities.